WHAT ENGLISH COLLOCATIONS TO TEACH FIRST TO INDONESIAN PRESCHOOL CHILDREN? A MINI-CORPUS BASED RESEARCH OF INDONESIAN CHILDREN'S STORYBOOKS - Maryani, Maryani (Indonesian Journal of Applied Linguistics, 2012)
Abstract: Frequent content words in a mini-corpus of 131 Indonesian children’s storybooks, which resulted in a corpus of 134, 320 words, were investigated. The result was used to identify what English collocations to teach first to Indonesian preschool children. The data were run through a collocation menu in MonoConc Pro, a corpus program. To identify the frequent collocations in the corpus, the preceding and following words from each frequent lemma were analyzed. All the data were calculated in terms of the whole corpus and normalized per 100,000 occurrences. The result showed that the children were already exposed to various collocations; however, it turned out that several English and Indonesian collocations were not similar in terms of syntax and morphology. Teachers cannot literally introduce those collocations to children. Key words: corpus, frequent collocation, content words